Strengthening Fishermen's Household Resilience through Business Diversification in Facing Climate Change in Hulaliu Village - Angela Ruban; Margie Wattimury; Eygner Gerald Talakua; Janer Sangaji; Mukhlis (Pascasarjana Universitas Mataram, 2026)
Climate change has a direct impact on the livelihoods of traditional fishermen, due to their high dependence on natural conditions and a lack of understanding of these environmental changes. Diversifying livelihoods based on local resources such as seaweed, shellfish, salt, coconuts, bananas, corn, bamboo, medicinal plants, or ornamental plants is a key strategy for strengthening the economic resilience of fishing households, especially during extreme weather conditions that can hinder fishing. This community service activity aimed to enhance understanding of climate change impacts on seasonal patterns and catches, as well as to increase knowledge regarding business diversification by utilizing local potential as alternative income sources for 12 fishermen and 10 fishermen' wives. The method employed was a community-based participatory approach that actively involved the fishers and their families in every stage of the activity. The implementation consisted of several stages: identifying problems and local potential, conducting a pre-test, delivering climate change education, organizing business diversification outreach, and administering a post-test. The results indicated a significant increase in participants' understanding before and after the material delivery, rising from 51.3% to 97.5%. This improvement demonstrates the effectiveness of the activity in equipping participants with foundational knowledge to mitigate climate change and strengthen household economies.